A Convenient Preparation of Fluorinating Reagent F‐TEDA Bearing Bisphenylsulfonylimide Counterion and Its Fluorination to Oxindoles. Issue 2 (9th December 2014) - Zhu, Wenhua; Hu, Xiaohui; Wang, Fajie; Yang, Xianjin; Wu, Xinyan
Abstract The direct preparation of a kind of fluorinating reagent 1 [F‐TEDA‐N(SO2Ph)2] was realized in high yield via the complexation of N‐fluorobenzenesulfonimide (NFSI) with 1‐(chloromethyl)‐1, 4‐diazabicyclo[2.2.2]octan‐1‐ium N′, N′‐bis‐(benzenesulfonylimide) salt. In its fluorination to oxindoles, the fluorinating products 6 were afforded in moderate to high yields.